2012
DOI: 10.1111/j.1745-6584.2012.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Removal from Natural Groundwater Using Cupric Oxide

Abstract: Groundwater is a main source of drinking water for some rural areas. People in these rural areas are potentially at risk from elevated levels of arsenic (As) due to a lack of water treatment facilities. The objectives of this study were to (1) measure As concentrations in approximately 50 groundwater samples from rural domestic wells in the western United States, (2) explore the potential of cupric oxide (CuO) particles in removal of As from groundwater samples under natural conditions (i.e., without adding co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…However, the concentration of calcium in the PBW is high enough that a nanoparticle-induced decrease may not have been apparent. It is still unlikely that the CuO-NPs used in this study are absorbing large amounts of calcium during processing, because there was no decrease in arsenic absorption capabilities of the CuO-NPs in PBW, which contains high levels of calcium compared to earlier studies with groundwater with a lower calcium concentrations 13 .…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…However, the concentration of calcium in the PBW is high enough that a nanoparticle-induced decrease may not have been apparent. It is still unlikely that the CuO-NPs used in this study are absorbing large amounts of calcium during processing, because there was no decrease in arsenic absorption capabilities of the CuO-NPs in PBW, which contains high levels of calcium compared to earlier studies with groundwater with a lower calcium concentrations 13 .…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies reported that CuO-NPs removed arsenic from groundwater 11,13,30,31 . This study supports these previous findings and also reports that CuO-NPs remove additional contaminants from PBW.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, the maximum adsorption capacity of CuO NPs was much higher than that of its bulk counterpart. The maximum adsorption capacity of CuO NPs was reported to be 26.9 mg/g CuO NPs for As(III) and 22.6 mg/g CuO NPs for As(V), whereas the maximum removal of As from water by bulk CuO was approximately 369 μg As/g CuO . Moreover, As(III) adsorption to CuO NPs showed greater dependence on pH (6–11) and ranged from 62 to 83%, whereas As(V) was relatively independent of pH in the range and consistent from 90 to 97%.…”
Section: Environmental Behavior Of Cuo Nps and Asmentioning
confidence: 99%